2010
DOI: 10.1209/0295-5075/91/45002
|View full text |Cite
|
Sign up to set email alerts
|

Generating a magnetic field by a rotating plasma

Abstract: In this paper we show, via an analytical study, new results for a rotating plasma generating a magnetic field. We study infinitely long cylindrical shells containing plasma. For a plasma of infinite conductivity we show that the existence of a magnetic field is compatible with the dynamics of two coaxial cylinders rotating at different uniform angular velocities, along with a single uniformly accelerated cylinder. In the case of finite conductivity, we show that under a series of constraints on the fluid chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In a previous work [6] the authors showed that a magnetic field can be generated in the laminar region of a fluid velocity under the condition ρ = ησµ, but such a condition is far from the usual condition of the celestial body and, more important, its magnitude would be of the order of B ∼ ΩR √ ρµ 0 where Ω is the rotational velocity, R is the radius of the outer core, and ρ is the density of the fluid in the outer core of Earth [7]. Inserting Earth's parameters would imply an intensity field of B ∼ 10 5 gauss that is very far from Earth's actual magnetic field value.…”
Section: Introductionmentioning
confidence: 90%
“…In a previous work [6] the authors showed that a magnetic field can be generated in the laminar region of a fluid velocity under the condition ρ = ησµ, but such a condition is far from the usual condition of the celestial body and, more important, its magnitude would be of the order of B ∼ ΩR √ ρµ 0 where Ω is the rotational velocity, R is the radius of the outer core, and ρ is the density of the fluid in the outer core of Earth [7]. Inserting Earth's parameters would imply an intensity field of B ∼ 10 5 gauss that is very far from Earth's actual magnetic field value.…”
Section: Introductionmentioning
confidence: 90%